Inferior gluteal artery perforator (IGAP) flap versus profunda artery perforator (PAP) flap as an alternative option for free autologous breast reconstruction. Issue 3 (March 2022) - Murphy, Declan C.; Razzano, Sergio; Wade, Ryckie G.; Haywood, Richard M.; Figus, Andrea
Summary: Background: When patients are unsuitable for deep inferior epigastric perforator (DIEP) flap breast reconstruction, the inferior gluteal artery perforator (IGAP) flap has been used as an alternative option. However, the profunda artery perforator (PAP) flap is also gaining popularity as an alternative to the DIEP flap for several reasons. This retrospective cohort study compares baseline characteristics, peri- and post-operative outcomes following IGAP flap and PAP flap breast reconstructions after mastectomy for cancer. Methods: In a single center in the UK, from September 2008 through December 2016, 43 women underwent IGAP Flap(s) breast reconstruction and 51 received PAP flap(s) breast reconstructions. Statistical analysis was performed to compare baseline, peri-operative and post-operative variables between the two reconstruction methods. Results: Perioperative complications requiring reoperation were experienced in women undergoing IGAP flap breast reconstructions only (21% versus 0%, p  = 0.001), principally due to the risk of total flap failure (12% versus 0%, p  = 0.01). Women undergoing IGAP flap breast reconstructions were at significantly higher odds of revision surgery (OR 17 [95% CI: 5.5-53], p  < 0.001), which was unchanged after adjusting for bilateral reconstructions (adjusted OR 18 [95% CI: 5.3-58], p  < 0.001). Conclusions: PAP flaps appear to be associated with significantly fewer complications and revision surgeries than IGAP flaps for breast reconstruction in women undergoing mastectomy for cancer and who are unsuitable for a DIEP flap breast reconstruction.